1999
DOI: 10.1093/ije/28.4.799
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and neurocysticercosis in an Andean community

Abstract: These findings confirm that T. solium NCC is a significant cause of epilepsy at the community level in Andean villages of Ecuador. It is important to initiate effective public health interventions to eliminate this infection, which may be responsible for at least half of the cases of reported epilepsy in Ecuador.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
1
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 23 publications
6
50
1
5
Order By: Relevance
“…This finding is in contrast with the observation by Cruz et al (1999) who found a higher proportion of female epileptics with positive Ab-Elisa results and who attributed it to food handling activities and their relationship with infection with cysticerci.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in contrast with the observation by Cruz et al (1999) who found a higher proportion of female epileptics with positive Ab-Elisa results and who attributed it to food handling activities and their relationship with infection with cysticerci.…”
Section: Discussioncontrasting
confidence: 99%
“…The most noticeable tip of this iceberg consists of people who harbor established, symptomatic central nervous system (CNS) disease-that is, neurocysticercosis. Below this tier is a larger population with established cysticercosis infection outside the CNS or in the CNS but without discernible symptoms, [7][8][9][10] and below this, there are many more people who were exposed to failed infections, but became seropositive. The presence of extremely high seroprevalence of Taenia solium antibodies in disease-endemic populations and relatively few symptomatic cases of neurocysticercosis was assumed to be a result of a largely asymptomatic infected human population, with minimal changes in prevalence over time.…”
mentioning
confidence: 99%
“…This could also explain the discrepant finding of high background levels of putatively inactive, calcified brain lesions in seronegative controls. [8][9][10] The incidence of exposure or infection must therefore be much higher than was previously suspected in order to balance the effect of transient antibody reactions and still maintain an equilibrium of high prevalence levels. The relationship between the transient antibody and exposure, current infection, or the development of immunity to future infection remains to be elucidated.…”
mentioning
confidence: 99%
“…Epileptic seizures were followed by headaches in 27.7% of people [58]. Headache in people with NCC can be acute or chronic, and presents as tension-type or migraine-like episodes [98,99]. Headache can also indicate raised intracranial pressure [90].…”
Section: Staging Pathology and Clinical Characteristics Of Neurocystmentioning
confidence: 99%